Pengaruh Model Pembelajaran Cooperative Integrated Reading and Composition (CIRC) Terhadap Hasil Belajar Bahasa Indonesia Kelas IV UPT SPF SD Negeri 106800 Hamparan Perak - Rizki, Miratanti; Malinda, Leni; Ramadhani, Mastari (Medan Resource Center, 2024)
This research aims to determine: 1) The Indonesian language learning outcomes of students using the conventional teaching model at UPT SPF SD Negeri 106800, 2) The learning outcomes of students using the CIRC (Cooperative Integrated Reading and Composition) learning model at UPT SPF SD Negeri 106800, 3) The influence of the CIRC learning model on the Indonesian language learning outcomes of fourth-grade students at UPT SPF SD Negeri 106800. This study is a quantitative experimental research using a quasi-experimental design (non-equivalent control group design) involving pretest and posttest activities. The research was conducted in two classes: the experimental class (Class IV-A with 15 students) and the control class (Class IV-B with 15 students). The findings indicate a significant effect of the CIRC learning model on student learning outcomes. The average learning outcome for students using the CIRC model was 83.33, while those using the conventional model scored 76.33. The results of the t-test showed Sig. (2-tailed) < 0.05 (0.00 < 0.05), indicating that the CIRC learning model significantly improves Indonesian language learning outcomes.